Women architects and politics : intersections between gender, power structures and architecture in the long 20th Century - Budde, Christina; Pepchinski, Mary (2022)
In the late 1960s, the feminist scholar Kate Millet broadly defined »politics« as arrangements of power which enable individuals collectively to assert authority over others. Taking this definition, case studies by scholars from Europe and Israel explore the gendered professional in the 20th century as she navigated arrangements of power-including organised religion, emancipation movements, cultural norms, and shifting forms of government-to practice architecture. Additional contributions reflect upon power structures in contemporary architectural education, practice, and history to propose other means of architectural knowledge, representation, and professional activity.